Perbandingan Aktivitas Antijamur Ekstrak dan Fraksi Daun Gelinggang (Cassia alata L.) Terhadap Malassezia globosa dan Microsporum canis - Wahyu Margi Sidoretno (LPPM Universitas Abdurrab, 2023)
Gelinggang (Cassia alata L.) leaves are traditionally used by Indonesian people to treat skin diseases such as ringworm, tinea versicolor and scabies. This study aims to determine the comparison of extract and fraction of gelinggang leaves against Malassezia globosa and Microsporum canis. The samples used were ethanol extract, n-hexane fraction, ethyl acetate fraction, ethanol fraction from gelinggang leaf. Based on phytochemical screening tests, flavonoids and alkaloids contained in gelinggang leaf ethyl acetate fraction and ethanol fraction. Terpenoids contained in the leaves gelinggang n-hexane fraction and ethyl acetate fraction. Saponins contained in the leaves gelinggang ethanol fraction. Phenolic contained in gelinggang leaf n-hexane fraction, ethyl acetate fraction and ethanol fraction. Antifungal activity testing using Kirby-Bauer method on Malassezia globosa obtained MIC with ethanol extract gelinggang leaf sample (1%) 10.4 mm; n-hexane fraction (1%) 7.8 mm; ethyl acetate fraction (1%) 16.3 mm; ethanol fraction (5%) 8,8 mm. Against Microsporum canis with gelinggang leaf sample ethanol extract (1%) obtained inhibition zone 15.5 mm; n-hexane fraction (1%) 9.9 mm; ethyl acetate fraction (1%) 18.2 mm; ethanol fraction (1%) 8.3 mm. It can be concluded that the extract and fraction gelinggang leaf able to inhibit are growth Malassezia globosa and Microsporum canis.